A systematic review on current and future prospects of 5G communications - Mounika Tummala; Punith Bekal; Pramod Kumar; Shalini Puri; Sanyog Rawat; Anjali Kumari (Cogent Engineering)
The evolution of mobile communication from 1G to 5G has revolutionized global connectivity, offering faster speed and lower latency. However, numerous challenges persist, hindering the full realization of 5G’s potential. Infrastructure investment remains a significant hurdle, particularly in rural areas, and concerns over energy consumption, regulatory obstacles, and health risks require careful consideration. Integration with legacy systems and ensuring data security adds to the complexity of deploying 5G networks. However, the future scope of 5G holds immense promise for driving Industry 4.0, global connectivity, and edge computing. To achieve these goals, collaborative efforts are needed to address research gaps and innovate solutions that affordably extend network coverage to rural areas and enhance cross-border interconnectivity. Implementing innovative financial models, enhancing energy efficiency, streamlining regulatory processes, ensuring robust data security, and fostering inclusive collaboration are crucial for overcoming 5G deployment challenges and unlocking its full potential.